Applied embedded electronics : design essentials for robust systems - Twomey, Jerry (Electronics engineer) (Sebastopol, CA : O'Reilly Media, Inc., 2024)
Embedded controller electronics are at the heart of virtually all modern electronic devices today with a market of more than $86 billion per year and growing. To serve the needs of designers creating products for this huge market, this practical book covers topics crucial for modern electronics design. Author Jerry Twomey examines the methods necessary to help you create a trouble-free integrated system for your product, with an emphasis on hardware design. You'll explore topics from the perspective of real-world applications, including discussions about non-ideal components, noise, and methods for avoiding problematic scenarios. This book guides you through all of the techniques listed, which are required for a reliable integrated system. Through extensive illustrations and minimal equations, anyone with an interest in electronics will quickly grasp the ideas discussed.
Essential concepts -- Architecting the system -- Robust digital communication -- Power systems -- Battery power -- Electromagnetic interference and electrostatic discharge -- Data converters : ADCs and DACs -- Driving peripheral devices -- Sensing peripheral devices -- Digital feedback control -- Schematic to PCB -- Software and coding -- Special systems and applications -- Creating great products.
Includes bibliographical references and index.
Keywords: Embedded computer systems; Systèmes enfouis (Informatique)